KONTRIBUSI MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR INSTALASI PENERANGAN LISTRIK SISWA SMK NEGERI 3 SINGARAJA - Intan, Ni Luh Gede Intan Adnya Swari; Ratnaya, I Gede Ratnaya; Mahardika, Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2024)
This research aims to examine the contribution of learning motivation and Learning discipline on the learning outcomes of electrical lighting installation for State Vocational School students 3 Singara, the research design used in this research is ex post facto with quantitative methods using data collection techniques observation, questionnaire and documentation methods, which the analysis uses simple regression analysis. The population in this study were students in class X1 and X11 majoring in Electrical Power Installation Engineering, SMK Negeri 3 Singaraja, engineering sampling using random sampling of 58 respondents, Based on the results of the analysis, it shows that (1) First hypothesis testing shows that there is a significant influence on learning motivation results of learning about electrical lighting in stallation for class XI and XII students at SMK Negeri 3 Singaraja (2) Testing the second hypothesis shows that learning discipline is not influence on learning outcomes in electrical lighting installation subjects (3) Learning discipline does not affect learning outcomes so no multiple correlation testing was carried out.